Holocene sedimentology in an isolation basin in the Larsemann Hills, East Antarctica - Mahesh, B.S.; Nair, Abhilash; Ghadi, Pooja; Warrier, Anish Kumar; Mohan, Rahul (Polar Science, 2021)
Holocene paleoenvironmental changes along the East Antarctic margin have been reconstructed using marine and lake sediment cores. Isolation basins in the coastal ice-free regions offer continuous sedimentary sequences to reconstruct marine-freshwater transitions and its environmental changes. In this study, we present the grain size (sand-silt-clay) and organic matter variations in a 51 cm radiocarbon-dated sediment core from Pup Lagoon, an isolation basin in Larsemann Hills (East Antarctica). The sediment core spans the last 6109 years and provides information on environmental changes in two different settings, i.e., (a) under the marine influence, and (b) as an isolated lake. Three cluster zones were identified viz., LZ1 (6109–2427 y BP: marine environment), LZ2 (2427–2101 y BP: transition zone) and LZ3 (2101–116 y BP: freshwater environment). Fine grain sediments (silt) are dominant in LZ1, indicating a strong hydrodynamic energy conditions affected by tidal currents with low organic matter. Higher sand content during the transition period (LZ2) indicates the strongest hydrodynamic condition and sediment deposition from sea ice. The increasing trend of OM (cyanobacterial benthic mat) beginning at ~ 2101 y BP suggests the isolation of the lake. The highest fine grained sediments (silt-clay) in LZ3 suggests lowered meltwater derived detritus in response to mild austral summer conditions during the Late Holocene. journal article